Neurologic involvement in seronegative primary Sjögren’s syndrome with positive minor salivary gland biopsy: a single-center experience - Hoshina, Yoji; Wong, Ka-Ho; Galli, Jonathan; Bacharach, Rae; Klein, Julia; Lebiedz-Odrobina, Dorota; Rose, John W.; Trump, Bryan; Hull, Christopher; Greenlee, John E.; Clardy, Stacey L. (Frontiers in Neurology, 2023)
Objective To assess the demographics, neurologic manifestations, comorbidities, and treatment of patients with seronegative primary Sjögren’s syndrome (pSS). Patients and Methods We conducted a retrospective chart review on patients with seronegative pSS evaluated by a neurologist at the University of Utah Health between January 2010 and October 2018. The diagnosis was based on characteristic symptoms, positive minor salivary gland biopsy according to the American-European Consensus Group 2002 criteria, and seronegative antibody status. Results Of 45 patients who met the study criteria, 42 (93.3%) were Caucasian, and 38 (84.4%) were female. The patients’ mean age at diagnosis was 47.8±12.6 (range 1371) years. Paresthesia, numbness and dizziness, and headache were noted in 40 (88.9%), 39 (86.7%), and 36 patients (80.0%), respectively. Thirty-four patients underwent brain magnetic resonance imaging. Of these, 18 (52.9%) showed scattered nonspecific periventricular and subcortical cerebral white matter T2/fluid-attenuated inversion recovery hyperintense foci. Twenty-nine patients (64.4%) presented to the neurology clinic prior to pSS diagnosis, and the median delay in diagnosis from the first neurology clinic visit was 5 (interquartile ranges 2.0–20.5) months. Migraine and depression were the most common comorbidities in 31 patients (68.9%). Thirty-six patients received at least one immunotherapy, and 39 were on at least one medication for neuropathic pain. Conclusion Patients often display various nonspecific neurological symptoms. Clinicians should express a high degree of skepticism regarding seronegative pSS and consider minor salivary gland biopsy to avoid delaying diagnosis, as undertreatment can affect patients’ quality of life.